Pengaruh Store Attribute Terhadap Loyalitas Wisatawan Dikontrol Oleh Motivasi Berbelanja - Astari, Bunga; Wibowo, Lili Adi; Ridwanudin, Oce (Universitas Pendidikan Indonesia, 2017)
Bandung is one of the cities which has many potentials in shopping tourism. Year after years the number of the shopping center in Bandung is increasing. Although shopping tourism in Bandung become the main destination for shopper but the customer loyalty is in a low state of condition. The customer more interest to try something new. So many new products that the competitors offered has caused the customers difficult to be loyal. By Creating the store attribute strategy is expected could increase the customer loyalty and could be more understand the shopper motives. This study is a descriptive and verificative and used explanatory survey method and cross sectional approach. The number of sample in this study were 111 respondents, those are the tourists who shopped in Bandung. The sampling technique that is used was simple random sampling. The Data analysis technique used is multiple regression. The independent variable in this research is the store attribute (X) which has three dimensions, those are store atmosphere (X1), convenience (X2), merchandise (X3), promotion (X4), interpersonal communication (X5), while the dependent variable is the loyalty (Y). Touristâ€™s responses to store attribute and loyalty considered sufficiently high, the majority of tourist has a hedonic shopping motives.Â Based on the result of this study, it shows that store attribute is influencing the touristâ€™s loyalty controlled by shopping motives.